Electromagnetic traction type anti-corrosion mortar steel bar and preparation method thereof

By using the Fe3O4-INT-LDH carrier driven by electromagnetic traction in reinforced concrete, the rust inhibitor is migrated directionally to the surface of the steel bar, solving the problems of weak and uncertain migration ability of traditional rust inhibitors, and achieving efficient and environmentally friendly rust prevention effect of steel bars.

CN116639900BActive Publication Date: 2025-04-18NANJING HYDRAULIC RES INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310659256.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-06
Publication Date
2025-04-18
Estimated Expiration
2043-06-06

AI Technical Summary

Technical Problem

Traditional rust inhibitors have weak migration ability and uncertain migration direction in concrete, resulting in waste of rust inhibitors and environmental pollution.

Method used

Through the co-precipitation method, the rust inhibitor of iron tetraoxide particles were combined with hydrotalcite intercalation rust inhibitors, and the directional migration of the rust inhibitors in the mortar was driven by electromagnetic traction, and the directional migration of the rust inhibitors to the surface of the steel bars was achieved by using Fe3O4-INT-LDH as the "transport" carrier.

Benefits of technology

It greatly improves the performance and comprehensive efficiency of rust inhibitors, reduces the waste of rust inhibitors, avoids environmental pollution, and significantly improves the rust prevention ability of steel bars.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116639900B_ABST
    Figure CN116639900B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of reinforced concrete rust inhibitors, and more specifically, to a kind of electromagnetic traction type anticorrosive mortar steel bar and its preparation method. In order to overcome the problem that the migration ability of traditional rust inhibitors is weak and the migration direction is uncertain, the present invention introduces an energized coil around the steel bar coated with mortar, so that the steel bar itself is magnetic, and uses ferroferric oxide as a "transportation" carrier to play a "transportation" role for the directional migration of the rust inhibitor. In order to enable the rust inhibitor to be stably combined with ferroferric oxide particles, and effectively exert the slow-release-solid chlorine effect of hydrotalcite intercalation rust inhibitor, the present invention combines ferroferric oxide, rust inhibitor and hydrotalcite by chemical synthesis means, and prepares ferroferric oxide-rust inhibitor-hydrotalcite (Fe3O4-INT-LDH) that can be driven by electromagnetic traction, and can greatly improve the performance and overall efficiency of the rust inhibitor through the dual effects of electromagnetic directional migration and anion recognition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of steel bar rust inhibitors, and in particular to an electromagnetic traction type anti-corrosion mortar steel bar and a preparation method thereof. Background Art

[0002] The steel bar corrosion problem caused by chloride ion erosion is one of the main reasons that affect the long-term service life of reinforced concrete structures. For the steel bar corrosion problem in concrete, the protective measures include coating, cathodic protection and adding rust inhibitors. Among them, adding rust inhibitors is a more common rust prevention measure.

[0003] Rust inhibitors are usually evenly mixed into the concrete structure during the concrete mixing stage, and then migrate to the surface of the steel bars through the migration and penetration of the rust inhibitor in the concrete structure to exert a rust-inhibiting effect. Hydrotalcite is a common layered material that has excellent anion exchange capacity and can load rust inhibitors through anion intercalation. When encountering chloride ion corrosion in concrete, hydrotalcite can effectively solidify the chloride ions while slowly releasing the rust inhibitor, exerting a synergistic effect.

[0004] However, both traditional rust inhibitors and hydrotalcite intercalated rust inhibitors have some obvious defects in their usage patterns. First, the rust inhibitors added to concrete are evenly dispersed in the concrete, and most of the rust inhibitors are difficult to automatically migrate to the surface of the steel bars, resulting in a large amount of waste of rust inhibitors. Secondly, the migration direction of the rust inhibitors in concrete is uncertain, and some rust inhibitors will migrate toward the surface of the concrete and eventually leak into the environment, causing pollution. Summary of the invention

[0005] In order to overcome the problems of weak migration ability and uncertain migration direction of traditional rust inhibitors, the present invention artificially introduces external electromagnetic force, uses ferroferric oxide as a "transportation" carrier, and plays a "transportation" role for the directional migration of the rust inhibitor. In order to enable the rust inhibitor to be stably combined with ferroferric oxide particles and effectively exert the slow-release-fixing chlorine effect of the hydrotalcite intercalation rust inhibitor, the present invention combines ferroferric oxide, rust inhibitor and hydrotalcite by chemical synthesis to prepare Fe3O4-INT-LDH, which can greatly improve the performance and overall efficiency of the rust inhibitor through the dual effects of electromagnetic directional migration and anion recognition.

[0006] In order to achieve the above objectives, the present invention adopts the following technical scheme: an electromagnetic traction type anti-corrosion mortar steel bar and a preparation method thereof, which are used for the anti-corrosion of reinforced concrete, generate a hydrotalcite-loaded rust inhibitor on the surface of ferroferric oxide particles by a coprecipitation method, and use electromagnetic traction to drive the directional migration of the rust-inhibiting component in the mortar, specifically comprising the following steps:

[0007] (1) Preparation of Fe3O4-INT-LDH:

[0008] a) firstly dissolving Mg(NO3)2·6H2O and Al(NO3)3·9H2O in deionized water to prepare a mixed salt solution; then adding ferrosoferric oxide particles into the salt solution and uniformly dispersing them by ultrasonication;

[0009] b) Then NaOH is mixed with the rust inhibitor solution to obtain an alkaline solution; then the salt solution containing ferroferric oxide particles is slowly dripped into the alkaline solution, and after the pH of the system is stabilized, the system temperature is increased under normal pressure and then aged. After the aging is completed, the precipitate is washed to neutrality and dried to obtain the synthetic product Fe3O4-INT-LDH;

[0010] (2) Preparation of electromagnetic traction anti-corrosion mortar steel bars:

[0011] a) Fe3O4-INT-LDH particles are uniformly dispersed in mortar, wherein water reducing agent and retarder are also added to the mortar. The mortar is then applied on the surface of the steel bars as a steel bar protective layer.

[0012] b) After the painting is completed, an energized coil is arranged around the mortar steel bar to introduce a magnetic field to induce the Fe3O4-INT-LDH particles to migrate to the steel bar. After the energized coil is removed, the steel bar mortar is cured in a curing box to prepare an electromagnetic traction type anti-corrosion mortar steel bar.

[0013] Furthermore, in step (1), the particle size of the ferrosoferric oxide particles is about 30 nm, and the mass concentration thereof in the solution is 0.5% to 1.5%.

[0014] Furthermore, in step (1), the specific process of adding the magnesium source and the aluminum source is as follows: weigh 0.03 mol Mg(NO3)2·6H2O and 0.01 mol Al(NO3)3·9H2O and dissolve them in 35 mL deionized water to prepare a mixed salt solution.

[0015] Furthermore, in step (1), the rust inhibitor is sodium monofluorophosphate or sodium molybdate.

[0016] Furthermore, in step (1), the specific process of preparing the alkaline solution is: adding 0.075 mol NaOH and 0.01 mol rust inhibitor to 140 mL deionized water to prepare an alkaline solution.

[0017] Furthermore, in step (1), the salt solution is slowly dripped into the alkaline solution, the dripping process lasts for more than 1 hour, the pH is maintained at about 10.5, and the whole process is in a state of vigorous stirring.

[0018] Furthermore, in step (1), the system temperature is raised to 60-85°C under normal pressure, the aging time is 3-12 hours, and the drying temperature after washing is 70°C, and the drying time is 24 hours.

[0019] Furthermore, in step (2), the amount of Fe3O4-INT-LDH particles in the mortar is 1% to 3% of the mass of cement; the water-cement ratio of the mortar is 0.45 to 0.55, and the mortar-sand ratio is 0.35 to 0.45. The water reducer and retarder are calcium lignin sulfonate and citric acid, respectively, and the amounts are 0.1% to 0.3% and 0.01% to 0.1% of the mass of cement, respectively. The thickness of the mortar coating is 3 to 12 mm.

[0020] Furthermore, in step (2), the coverage length of the energized coil is half of the length of the steel bar, and the coil moves repeatedly along the steel bar during the energization process. The energization time is 0.5 to 12 hours.

[0021] Furthermore, in step (2), after the energized coil is removed, the steel mortar curing temperature is 20° C., the curing humidity is 90%, and the curing time is 7 days.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. To solve the problem of the difficulty of spontaneous migration of rust inhibitors in cement-based materials, the present invention combines Fe3O4 particles with hydrotalcite intercalation rust inhibitors through a co-precipitation method. Under the influence of an external energized coil, the steel bars become magnetic and adsorb the Fe3O4 particles in the mortar toward the center of the steel bars. The hydrotalcite intercalation rust inhibitor can be "transported" to the vicinity of the steel bar surface, effectively solving the problem of the difficulty of spontaneous migration of rust inhibitors in cement-based materials.

[0024] 2. When the rust inhibitor is directly added to the cement-based material, the migration direction of the rust inhibitor is not fixed. A part of the rust inhibitor will migrate to the surface of the steel bar until it leaks into the environment. On the one hand, this pollutes the environment, and on the other hand, it causes waste of rust inhibitors and increases economic costs. The present invention provides a centripetal driving force around the steel bars based on the electromagnetic traction effect, so that all rust inhibitors migrate centripetally around the steel bars in a consistent manner, effectively solving the problem of non-directional migration of rust inhibitors in cement-based materials. In addition, traditional rust inhibitors are incorporated into the concrete structure as a whole, which results in a large actual amount of rust inhibitor added. The present invention incorporates the rust-inhibiting component into the mortar layer, which greatly reduces the actual amount of rust inhibitor added.

[0025] 3. The electromagnetic traction type anti-corrosion mortar steel bars proposed in the present invention can simultaneously exert the dual targeting effects of electromagnetic traction and the slow-release-fixed chlorine effect of the hydrotalcite intercalation rust inhibitor, which can greatly improve the anti-rust ability of the steel bars. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1Schematic diagram of the open circuit potential of the electromagnetic traction type anti-corrosion mortar steel bars in this embodiment.

[0027] Figure 2 It is a schematic diagram of the rust prevention efficiency of the electromagnetic traction type anti-corrosion mortar steel bars in this embodiment. DETAILED DESCRIPTION

[0028] In order to better explain the present invention, the technical solution of the present invention is further explained below in conjunction with the accompanying drawings and specific embodiments. It should be noted that all technical and scientific terms used in the present invention have the same meanings as those commonly understood by ordinary technicians in the technical field to which the present invention belongs.

[0029] Example 1

[0030] (1) Preparation of Fe3O4-INT-LDH:

[0031] a) Weigh 0.03 mol Mg(NO3)2·6H2O and 0.01 mol Al(NO3)3·9H2O and dissolve them in 35 mL deionized water to prepare a mixed salt solution; then add ferroferric oxide particles into the salt solution and disperse them evenly by ultrasonication; the particle size of the ferroferric oxide particles is about 30 nm, and the mass concentration of the ferroferric oxide particles in the solution is 0.5%.

[0032] b) Then mix 0.075 mol NaOH, 0.01 mol sodium monofluorophosphate rust inhibitor and 140 mL deionized water to obtain an alkaline solution; then slowly drip the salt solution containing ferrosoferric oxide particles into the alkaline solution, and the dripping process lasts for more than 1 hour. When the pH of the system stabilizes at about 10.5, the whole process is in a state of vigorous stirring. After raising the system temperature to 60°C under normal pressure, age for 3 hours. After the aging is completed, wash the precipitate to neutrality, and then bake at 70°C for 24 hours to obtain the synthetic product Fe3O4-INT-LDH;

[0033] (2) Preparation of electromagnetic traction anti-corrosion mortar steel bars:

[0034] a) Fe3O4-INT-LDH particles are uniformly dispersed in mortar, and the dosage of Fe3O4-INT-LDH particles is 1% of the mass of cement, wherein a water reducer and a retarder are also added to the mortar. The water reducer and the retarder are calcium lignin sulfonate and citric acid, respectively, and the dosage is 0.1% and 0.01% of the mass of cement, respectively. The water-cement ratio of the mortar is 0.45, and the mortar-sand ratio is 0.35. Then the mortar is applied to the surface of the steel bar as a steel bar protective layer. The thickness of the mortar coating is 3 mm.

[0035] b) After the painting is completed, an energized coil is arranged around the mortar steel bar, and a magnetic field is introduced to induce the Fe3O4-INT-LDH particles to migrate to the steel bar. The coverage length of the energized coil is half the length of the steel bar, and the coil moves repeatedly along the steel bar during the energization process. The power-on time is 0.5 hours. After the coil is removed after the power-on, the steel bar mortar is cured in a curing box at a curing temperature of 20°C, a curing humidity of 90%, and a curing time of 7 days to prepare an electromagnetic traction type anti-corrosion mortar steel bar.

[0036] Example 2

[0037] (1) Preparation of Fe3O4-INT-LDH:

[0038] a) Weigh 0.03 mol Mg(NO3)2·6H2O and 0.01 mol Al(NO3)3·9H2O and dissolve them in 35 mL deionized water to prepare a mixed salt solution; then add ferroferric oxide particles into the salt solution and disperse them evenly by ultrasonication; the particle size of the ferroferric oxide particles is 30 nm, and the mass concentration thereof in the solution is 1%.

[0039] b) Then mix 0.075 mol NaOH, 0.01 mol sodium monofluorophosphate rust inhibitor and 140 mL deionized water to obtain an alkaline solution; then slowly drip the salt solution containing ferrosoferric oxide particles into the alkaline solution, and the dripping process lasts for more than 1 hour. When the pH of the system stabilizes at about 10.5, the whole process is in a state of vigorous stirring. After raising the system temperature to 75°C under normal pressure, age for 6 hours. After the aging is completed, wash the precipitate to neutrality, and then bake at 70°C for 24 hours to obtain the synthetic product Fe3O4-INT-LDH;

[0040] (2) Preparation of electromagnetic traction anti-corrosion mortar steel bars:

[0041] a) Fe3O4-INT-LDH particles are uniformly dispersed in mortar, and the dosage of Fe3O4-INT-LDH particles is 1% of the mass of cement, wherein a water reducer and a retarder are also added to the mortar. The water reducer and the retarder are calcium lignin sulfonate and citric acid, respectively, and the dosage is 0.2% and 0.05% of the mass of cement, respectively. The water-cement ratio of the mortar is 0.5, and the mortar-sand ratio is 0.4. Then the mortar is applied to the surface of the steel bar as a steel bar protective layer. The thickness of the mortar coating is 7 mm.

[0042] b) After the painting is completed, an energized coil is arranged around the mortar steel bar, and a magnetic field is introduced to induce the Fe3O4-INT-LDH particles to migrate to the steel bar. The coverage length of the energized coil is half the length of the steel bar, and the coil moves repeatedly along the steel bar during the energization process. The power-on time is 6 hours. After the coil is removed after the power-on, the steel bar mortar is cured in a curing box at a curing temperature of 20°C, a curing humidity of 90%, and a curing time of 7 days to prepare an electromagnetic traction type anti-corrosion mortar steel bar.

[0043] Example 3

[0044] (1) Preparation of Fe3O4-INT-LDH:

[0045] a) Weigh 0.03 mol Mg(NO3)2·6H2O and 0.01 mol Al(NO3)3·9H2O and dissolve them in 35 mL deionized water to prepare a mixed salt solution; then add ferroferric oxide particles into the salt solution and disperse them evenly by ultrasonication; the particle size of the ferroferric oxide particles is 30 nm, and the mass concentration of the ferroferric oxide particles in the solution is 1.5%.

[0046] b) Then mix 0.075 mol NaOH, 0.01 mol sodium molybdate rust inhibitor and 140 mL deionized water to obtain an alkaline solution; then slowly drip the salt solution containing ferrosoferric oxide particles into the alkaline solution, and the dripping process lasts for more than 1 hour. When the pH of the system stabilizes at 10.5, the whole process is in a state of vigorous stirring. After raising the system temperature to 85°C under normal pressure, age for 12 hours. After the aging is completed, wash the precipitate to neutrality, and then bake at 70°C for 24 hours to obtain the synthetic product Fe3O4-INT-LDH;

[0047] (2) Preparation of electromagnetic traction anti-corrosion mortar steel bars:

[0048] a) Fe3O4-INT-LDH particles are uniformly dispersed in mortar, and the dosage of Fe3O4-INT-LDH particles is 3% of the cement mass. A water reducer and a retarder are also added to the mortar. The water reducer and the retarder are calcium lignin sulfonate and citric acid, respectively, and the dosage is 0.3% and 0.1% of the cement mass, respectively. The water-cement ratio of the mortar is 0.55, and the mortar-sand ratio is 0.45. Then the mortar is applied to the surface of the steel bar as a steel bar protective layer. The thickness of the mortar coating is 12 mm.

[0049] b) After the painting is completed, an energized coil is arranged around the mortar steel bar, and a magnetic field is introduced to induce the Fe3O4-INT-LDH particles to migrate to the steel bar. The coverage length of the energized coil is half the length of the steel bar, and the coil moves repeatedly along the steel bar during the energization process. The power-on time is 12 hours. After the coil is removed after the power-on, the steel bar mortar is cured in a curing box at a curing temperature of 20°C, a curing humidity of 90%, and a curing time of 7 days to prepare an electromagnetic traction type anti-corrosion mortar steel bar.

[0050] Example 4

[0051] (1) Preparation of Fe3O4-INT-LDH:

[0052] a) Weigh 0.03 mol Mg(NO3)2·6H2O and 0.01 mol Al(NO3)3·9H2O and dissolve them in 35 mL deionized water to prepare a mixed salt solution; then add ferroferric oxide particles into the salt solution and disperse them evenly by ultrasonication; the particle size of the ferroferric oxide particles is about 30 nm, and the mass concentration of the ferroferric oxide particles in the solution is 1%.

[0053] b) Then mix 0.075 mol NaOH, 0.01 mol sodium molybdate rust inhibitor with 140 mL deionized water to obtain an alkaline solution; then slowly drip the salt solution containing ferrosoferric oxide particles into the alkaline solution, and the dripping process lasts for more than 1 hour. When the pH of the system stabilizes at about 10.5, the whole process is in a state of vigorous stirring. After raising the system temperature to 70°C under normal pressure, age for 3 hours. After the aging is completed, wash the precipitate to neutrality, and then bake at 70°C for 24 hours to obtain the synthetic product Fe3O4-INT-LDH;

[0054] (2) Preparation of electromagnetic traction anti-corrosion mortar steel bars:

[0055] a) Fe3O4-INT-LDH particles are uniformly dispersed in mortar, and the dosage of Fe3O4-INT-LDH particles is 2% of the mass of cement, wherein a water reducer and a retarder are also added to the mortar. The water reducer and the retarder are calcium lignin sulfonate and citric acid, respectively, and the dosage is 0.3% and 0.01% of the mass of cement, respectively. The water-cement ratio of the mortar is 0.55, and the mortar-sand ratio is 0.35. Then the mortar is applied to the surface of the steel bar as a steel bar protective layer. The thickness of the mortar coating is 9 mm.

[0056] b) After the painting is completed, an energized coil is arranged around the mortar steel bar, and a magnetic field is introduced to induce the Fe3O4-INT-LDH particles to migrate to the steel bar. The coverage length of the energized coil is half the length of the steel bar, and the coil moves repeatedly along the steel bar during the energization process. The power-on time is 6 hours. After the coil is removed after the power-on, the steel bar mortar is cured in a curing box at a curing temperature of 20°C, a curing humidity of 90%, and a curing time of 7 days to prepare an electromagnetic traction type anti-corrosion mortar steel bar.

[0057] Example 5

[0058] (1) Preparation of Fe3O4-INT-LDH:

[0059] a) Weigh 0.03 mol Mg(NO3)2·6H2O and 0.01 mol Al(NO3)3·9H2O and dissolve them in 35 mL deionized water to prepare a mixed salt solution; then add ferroferric oxide particles into the salt solution and disperse them evenly by ultrasonication; the particle size of the ferroferric oxide particles is 30 nm, and the mass concentration of the ferroferric oxide particles in the solution is 1.5%.

[0060] b) Then mix 0.075 mol NaOH, 0.01 mol sodium monofluorophosphate rust inhibitor and 140 mL deionized water to obtain an alkaline solution; then slowly drip the salt solution containing ferrosoferric oxide particles into the alkaline solution, and the dripping process lasts for more than 1 hour. When the pH of the system stabilizes at about 10.5, the whole process is in a state of vigorous stirring. After raising the system temperature to 85°C under normal pressure, age for 12 hours. After the aging is completed, wash the precipitate to neutrality, and then bake at 70°C for 24 hours to obtain the synthetic product Fe3O4-INT-LDH;

[0061] (2) Preparation of electromagnetic traction anti-corrosion mortar steel bars:

[0062] a) Fe3O4-INT-LDH particles are uniformly dispersed in mortar, and the dosage of Fe3O4-INT-LDH particles is 3% of the cement mass. A water reducer and a retarder are also added to the mortar. The water reducer and the retarder are calcium lignin sulfonate and citric acid, respectively, and the dosage is 0.2% and 0.05% of the cement mass, respectively. The water-cement ratio of the mortar is 0.45, and the mortar-sand ratio is 0.45. Then the mortar is applied to the surface of the steel bar as a steel bar protective layer. The thickness of the mortar coating is 12 mm.

[0063] b) After the painting is completed, an energized coil is arranged around the mortar steel bar, and a magnetic field is introduced to induce the Fe3O4-INT-LDH particles to migrate to the steel bar. The coverage length of the energized coil is half of the length of the steel bar, and the coil moves repeatedly along the steel bar during the energization process. The power-on time is 9 hours. After the coil is removed after the power-on, the steel bar mortar is cured in a curing box at a curing temperature of 20°C, a curing humidity of 90%, and a curing time of 7 days to prepare an electromagnetic traction type anti-corrosion mortar steel bar.

[0064] Example 6

[0065] (1) Preparation of Fe3O4-INT-LDH:

[0066] a) Weigh 0.03 mol Mg(NO3)2·6H2O and 0.01 mol Al(NO3)3·9H2O and dissolve them in 35 mL deionized water to prepare a mixed salt solution; then add ferroferric oxide particles into the salt solution and disperse them evenly by ultrasonication; the particle size of the ferroferric oxide particles is 30 nm, and the mass concentration of the ferroferric oxide particles in the solution is 0.5%.

[0067] b) Then mix 0.075 mol NaOH, 0.01 mol sodium molybdate rust inhibitor and 140 mL deionized water to obtain an alkaline solution; then slowly drip the salt solution containing ferrosoferric oxide particles into the alkaline solution, and the dripping process lasts for more than 1 hour. When the pH of the system stabilizes at about 10.5, the whole process is in a state of vigorous stirring. After raising the system temperature to 70°C under normal pressure, age for 6 hours. After the aging is completed, wash the precipitate to neutrality, and then bake at 70°C for 24 hours to obtain the synthetic product Fe3O4-INT-LDH;

[0068] (2) Preparation of electromagnetic traction anti-corrosion mortar steel bars:

[0069] a) Fe3O4-INT-LDH particles are uniformly dispersed in mortar, and the dosage of Fe3O4-INT-LDH particles is 2% of the cement mass. A water reducer and a retarder are also added to the mortar. The water reducer and the retarder are calcium lignin sulfonate and citric acid, respectively, and the dosage is 0.3% and 0.1% of the cement mass, respectively. The water-cement ratio of the mortar is 0.45, and the mortar-sand ratio is 0.45. Then the mortar is applied to the surface of the steel bar as a steel bar protective layer. The thickness of the mortar coating is 6 mm.

[0070] b) After the painting is completed, an energized coil is arranged around the mortar steel bar, and a magnetic field is introduced to induce the Fe3O4-INT-LDH particles to migrate to the steel bar. The coverage length of the energized coil is half the length of the steel bar, and the coil moves repeatedly along the steel bar during the energization process. The power-on time is 6 hours. After the coil is removed after the power-on, the steel bar mortar is cured in a curing box at a curing temperature of 20°C, a curing humidity of 90%, and a curing time of 7 days to prepare an electromagnetic traction type anti-corrosion mortar steel bar.

[0071] Comparative Example 1

[0072] Anti-corrosion mortar steel bars were prepared according to the method in step (2) of Example 1, but no Fe3O4-INT-LDH particles were added and no energized coil was arranged.

[0073] Comparative Example 2

[0074] Anti-corrosion mortar steel bars were prepared according to the method in step (2) of Example 6, but no Fe3O4-INT-LDH particles were added and no energized coil was arranged.

[0075] Rust resistance test:

[0076] The prepared electromagnetic traction type anti-corrosion mortar steel bar was immersed in a corrosion solution, wherein the corrosion solution was composed of a 3% mass concentration NaCl solution. The anti-corrosion performance of the electromagnetic traction type anti-corrosion mortar steel bar after being immersed in the corrosion solution for different time periods was tested by electrochemical means. Figure 1 The open circuit potential data and Figure 2 It can be seen from the rust-proof efficiency data that the anti-corrosion performance of the electromagnetic traction anti-corrosion mortar steel bar system proposed in the present invention is significantly better than that of the ordinary mortar steel bars in the comparative example. On the one hand, this is because the energized coil introduces a magnetic field, which makes the ferroferric oxide a "transport" carrier, and plays a "transport" role for the directional migration of the rust inhibitor, so that the rust inhibitor can directly play an anti-corrosion role around the steel bars. On the other hand, the slow-release-chlorine-fixing effect of the hydrotalcite intercalation rust inhibitor also effectively improves the anti-corrosion performance of the mortar.

[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing electromagnetic traction type anti-corrosion mortar steel bars, used for anti-corrosion of reinforced concrete, characterized in that: The hydrotalcite-loaded rust inhibitor is generated on the surface of the ferroferric oxide particles by a coprecipitation method, and the directional migration of the rust-inhibiting component in the mortar is driven by electromagnetic traction, which specifically includes the following steps: (1) Preparation of Fe3O4-INT-LDH: a) firstly dissolving a magnesium source and an aluminum source in deionized water to prepare a mixed salt solution; then adding ferroferric oxide particles into the mixed salt solution and uniformly dispersing the particles by ultrasonication; b) then mixing NaOH with the rust inhibitor solution to obtain an alkaline solution; then slowly dripping the mixed salt solution with ferroferric oxide particles into the alkaline solution, and after the pH of the system is stabilized, raising the system temperature under normal pressure and aging, after the aging is completed, washing the precipitate to neutrality, and drying to obtain the synthetic product Fe3O4-INT-LDH; (2) Preparation of electromagnetic traction anti-corrosion mortar steel bars: a) Fe3O4-INT-LDH particles are uniformly dispersed in mortar, wherein a water reducer and a retarder are added to the mortar, and then the mortar is used as a steel bar protective layer and applied on the steel bar surface; b) After the painting is completed, an energized coil is arranged around the mortar steel bars to introduce a magnetic field to induce the Fe3O4-INT-LDH particles to migrate to the steel bars; after the energized coil is removed, the steel bar mortar is cured in a curing box to prepare an electromagnetic traction type anti-corrosion mortar steel bar.

2. The method for preparing an electromagnetic traction type anti-corrosion mortar steel bar according to claim 1, characterized in that: In the step (1), the particle size of the ferrosoferric oxide particles is 30 nm, and the mass concentration thereof in the solution is 0.5% to 1.5%.

3. The method for preparing an electromagnetic traction type anti-corrosion mortar steel bar according to claim 1, characterized in that: In the step (1), the magnesium source is Mg(NO3)2·6H2O, and the aluminum source is Al(NO3)3·9H2O; the specific process of adding the magnesium source and the aluminum source is: weighing 0.03 mol Mg(NO3)2·6H2O and 0.01 mol Al(NO3)3·9H2O and dissolving them in 35 mL deionized water to prepare a mixed salt solution.

4. The method for preparing an electromagnetic traction type anti-corrosion mortar steel bar according to claim 1, characterized in that: In the step (1), the specific process of preparing the alkaline solution is: adding 0.075 mol NaOH and 0.01 mol rust inhibitor to 140 mL of deionized water to prepare an alkaline solution.

5. A method for preparing an electromagnetic traction type anti-corrosion mortar steel bar according to claim 1 or 4, characterized in that: The rust inhibitor is sodium monofluorophosphate or sodium molybdate.

6. The method for preparing an electromagnetic traction type anti-corrosion mortar steel bar according to claim 1, characterized in that: In the step (1), the salt solution is slowly dripped into the alkaline solution, the dripping process lasts for more than 1 hour, the pH is maintained at 10.5, and the whole process is in a state of vigorous stirring.

7. The method for preparing electromagnetic traction type anti-corrosion mortar steel bars according to claim 1, characterized in that: In the step (1), the system temperature is raised to 60-85°C under normal pressure, the aging time is 3-12 hours, and the drying temperature after washing is 70°C, and the drying time is 24 hours.

8. The method for preparing electromagnetic traction type anti-corrosion mortar steel bars according to claim 1, characterized in that: In the step (2), the dosage of Fe3O4-INT-LDH particles in the mortar is 1% to 3% of the mass of cement; the water-cement ratio of the mortar is 0.45 to 0.55, and the mortar-sand ratio is 0.35 to 0.45; the water reducer and retarder are calcium lignin sulfonate and citric acid, respectively, and the dosages are 0.1% to 0.3% and 0.01% to 0.1% of the mass of cement, respectively; and the thickness of the mortar coating is 3 to 12 mm.

9. The method for preparing electromagnetic traction type anti-corrosion mortar steel bars according to claim 1, characterized in that: In the step (2), the coverage length of the energized coil is half the length of the steel bar, and the coil moves repeatedly along the steel bar during the energization process. The energization time is 0.5 to 12 hours.

10. The method for preparing electromagnetic traction type anti-corrosion mortar steel bars according to claim 1, characterized in that: In the step (2), after the energized coil is removed, the steel mortar curing temperature is 20° C., the curing humidity is 90%, and the curing time is 7 days.

Citation Information

Patent Citations

  • Preparation method and preparation device of cationic electromigration imidazoline concrete reinforcing bar corrosion inhibitor

    CN102924378A

  • Hydrotalcite intercalation chloride ion probe modified triazole corrosion inhibitor compound containing Schiff base and application thereof

    CN107986663A